Cutaneous Epithelioid Malignant Peripheral Nerve Sheath Tumor: A Case Report - D'Angelis, MD, PhD, Christopher A.; Crossland, MD, David M. (North American Journal of Medicine and Science, 2018)
Malignant peripheral nerve sheath tumor (MPNST) is a rare soft tissue sarcoma arising from neuroectoderm-derived cells comprising the outer coverings of peripheral nerves. Given the diverse cell types comprising the peripheral nerve sheath, both benign and malignant nerve sheath tumors display a wide range of histologic appearances. MPNST can arise either in association with proximal nerve trunks at deep body sites, or from distal nerve branches residing within skin and subcutaneous tissues. Overall, roughly 50% of MPNST arise in patients with neurofibromatosis type I. The remainder occur sporadically. We report herein a rare epithelioid example of MPNST arising sporadically within a cutaneous neurofibroma. We also offer a brief clinico-pathologic review of MPNST, including diagnostic workup, differential interpretation, treatment and prognosis. [N A J Med Sci. 2018;11(1):15-18. DOI: 10.7156/najms.2018.110115]